Analisa Deret Fourier Harmonisa Yang Dihasilkan Komputer Dan Laptop Menggunakan Simulasi Matlab/Simulink - Frensius; Silalahi, Eva Magdalena; Purba, Robinson (Prodi Teknik Elektro FT UKI, 2023)
Harmonics are multiples of the base frequency (50 Hz) in electrical energy systems, resulting from increased use of nonlinear loads in industry, offices, education and households, resulting in increased harmonic distortion in distribution networks. Computers and laptops are nonlinear loads that are a source of harmonic currents in electrical systems and are widely used by the public. High harmonics can damage electrical equipment. This study discusses harmonic problems caused by computers and laptops of different brands, in order to know the values of THDv, THDi, dominant order THDi, current harmonic wave equations and current waveforms. To conduct this study, PQA Kyoritsu KEW 6315 measurement data was analyzed using the Fourier series method and then a simulation of FFT Matlab Simulink was carried out. The results of this study show that the THDv values on computers and laptops of different brands, as a whole meet the IEEE 519-2014 standard, while the THDi values range from 80% to 86.96% which do not meet the IEEE 519-2014 standard. The dominant harmonic current order generated by computers and laptops of different brands has the same trend pattern in the dominant harmonic current order that occurs in the 3rd, 5th, 7th and 9th order, where the 3rd order has the highest dominant THDi value with a range of values between 40% to 52.17%. Also obtained is the wave equation of harmonic currents generated by computers and laptops using the Fourier series based on the same order of dominant harmonic currents from the measurement results, namely in the 1st, 3rd, 5th, 7th, and 9th order.